Design, user experience, and usability. design thinking and methods : 5th International Conference, DUXU 2016, held as part of HCI International 2016, Toronto, Canada, July 17-22, 2016, Proceedings /: design thinking and methods : 5th International Conference, DUXU 2016, held as part of HCI International 2016, Toronto, Canada, July 17-22, 2016, Proceedings. Part I : (2016) - Unknown
No abstract available